2005
DOI: 10.2106/jbjs.d.02710
|View full text |Cite
|
Sign up to set email alerts
|

Management of Mason Type-III Radial Head Fractures with a Titanium Prosthesis, Ligament Repair, and Early Mobilization

Abstract: The results of treatment of Mason type-III radial head fractures with a monoblock titanium radial head prosthesis and soft-tissue reconstruction are satisfactory. Early mobilization of the elbow is important for the restoration of elbow range of motion and function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 13 publications
1
21
0
1
Order By: Relevance
“…Depending on the fracture pattern and associated soft-tissue injury, several types of treatment exist for fractured radial head [2,17]. The radial head prosthesis used in this study for comminuted radial head fractures has an uncemented titanium stem, a 15°angulated neck, is modular, and has a pyrocarbon head [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the fracture pattern and associated soft-tissue injury, several types of treatment exist for fractured radial head [2,17]. The radial head prosthesis used in this study for comminuted radial head fractures has an uncemented titanium stem, a 15°angulated neck, is modular, and has a pyrocarbon head [1].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to restore radiocapitellar contact through repair or replacement of the radial head when treating unstable fracture dislocations of the elbow, such as those associated with injury of the interosseous ligament of the forearm (an Essex-Lopresti lesion) or posterior dislocation of the elbow with fractures of the radial head and coronoid process (the so-called terrible triad of the elbow [20]. Biomechanical studies have demonstrated that metallic prostheses can reproduce the loads across the elbow more closely than silastic prostheses [2]. Acrylic, stainless steel, silastic, pyrocarbon, and articulating CoCr prostheses have been developed, and a variety of results have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Because today's standards demand a greater degree of satisfactory function, ORIF is being widely used, and radial head prosthesis replacement is used in selected cases. Some authors believe that the radial head is not only important for humeroradial joint [1,14], but also for the stability of distal ulnoradial joint. In fractures of the radial head, especially complicated with forearm soft tissue injury, proximal migration of radius appears frequently and results in wrist strength weakening and chronic elbow pain.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, several models of radial head prosthesis are in use, including monopolar, bipolar, cemented, or press-fit implants. Regardless of design, recent literature has favored metal prostheses [1,24,30,36,37] despite evidence of altered joint contact pressures in radiocapitellar articulations involving metallic implants [18]. ''Overstuffing'' as a result of an excessively large prosthesis has received considerable attention [4,40] and problems of persistent pain and radiographic evidence of arthritis ( Fig.…”
Section: Introductionmentioning
confidence: 99%